The lexicon of Vannamei shrimp farming in Blendung Village, Ulujami District, Pemalang Regency: An ethnolinguistic study - Rismalasari, Dwi; Fateah, Nur (Universitas Dian Nuswantoro, 2025)
This research is motivated by the existence of a specialized lexicon in the field of vannamei shrimp farming that is frequently used by the community of Blendung Village, Ulujami District, Pemalang Regency. The objectives of this study are (1) to explore the knowledge regarding the meanings within the cultural lexicon of vannamei shrimp farming in Blendung Village, and (2) to describe the community's perspective on the tradition of vannamei shrimp farming. This study employs a qualitative descriptive method with an ethnolinguistic approach to understand the lexicon. The methodology of this research consists of three stages: data collection, data analysis, and data presentation. The data collection methods employed include interviews and participatory observation. The research findings lead to the following conclusions: (1) twelve lexicons related to tools were identified, (2) seven lexicons pertaining to materials were found, (3) eighteen lexicons associated with the processes of vannamei shrimp farming were discovered, and (4) six lexicons for classifying the naming of shrimp conditions were identified. Each of these lexicons emerged due to the diversity of tools, materials, processes, and naming conventions related to shrimp farming utilized by the local community. This research is beneficial for understanding the lexicons associated with vannamei shrimp farming in Blendung Village, thereby providing insights into the community's perspective on this practice.